GMO and human health - Vyshniak, L. (ТДАТУ, 2018)
UK: У статті розглянуто проблеми впливу ГМО організмів на здоров ’я людини, визначено негативні наслідки використання генетично-модифікованих організмів та побічні ефекти їх впливу на здоров ’я людини. EN: The problems of GMO organisms effect on human health have been considered in the article, negative consequences of the use of genetically modified organisms have been identified as well as their side effects on human health
Keywords: здоров ’я людини; використання генетично-модифікованих організмів; problems of GMO organisms effect on human; modified organisms have